2019
DOI: 10.1101/698480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TMT-Opsins differentially modulate medaka brain function in a context-dependent manner

Abstract: One Sentence SummaryTwo medakafish non-visual c-type Opsins interact non-additively, impacting the levels of the preprohormone sst1b, as well as the voltage-gated sodium channel subunit scn12aa and-at least in part independently of the eyes-the amount of larval day-time rest. AbstractVertebrate behavior is strongly influenced by light. Photoreceptors, encoded by Opsins, are present inside the vertebrate brain and peripheral tissues. Their non-visual functions are largely enigmatic.We focus on tmt-opsin1b and 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Extraretinal opsins are found in the zebrafish brain (Fischer et al, 2013), and deep brain photoreceptors have been shown to influence light‐mediated behavior (Fernandes et al, 2012; Fischer et al, 2013; Fontinha et al, 2020). Moreover, the specific SIN marker LCR RH2 ‐RH2‐2:GFP was generated by linking GFP to the green cone opsin enhancer.…”
Section: Discussionmentioning
confidence: 99%
“…Extraretinal opsins are found in the zebrafish brain (Fischer et al, 2013), and deep brain photoreceptors have been shown to influence light‐mediated behavior (Fernandes et al, 2012; Fischer et al, 2013; Fontinha et al, 2020). Moreover, the specific SIN marker LCR RH2 ‐RH2‐2:GFP was generated by linking GFP to the green cone opsin enhancer.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic zebrafish variants with altered photoreceptor distributions would thus be a valuable tool for further studies. Recent studies suggest that melanopsin-expressing ganglion cells also contribute to form vision (59,60), and melanopsins as well as a plethora of other opsins are expressed in the zebrafish retina and brain (61,62). It is therefore possible that photoreception via opsin-expressing neurons in the inner retina contributes to zebrafish OKR as well.…”
Section: Discussionmentioning
confidence: 99%